Controlling emissive behaviour through molecular design: 2,3-bis(2,5-dimethylthiophen-3-yl)quinoxalines with variable fluorene substitution - Loghina, Liudmila; Jancalek, Jiri; Houdek, Jakub; Zmrhalova, Zuzana; Jambor, Roman; Vlcek, Miroslav (Royal Society of Chemistry, 2025)
We report a new family of donor-acceptor-donor (D-A-D) chromophores based on 2,3-bis(2,5-dimethylthiophen-3-yl)quinoxaline, where the electronic and steric environment is tuned through fluorene substituents at the 5,8-positions. Variation of the 9,9-substituents (aryl, branched alkyl, and spiro-linked groups) enables systematic modulation of solubility, conformational rigidity, and intermolecular interactions while preserving the electron-deficient quinoxaline core. All synthesized derivatives (DMTQ1 - DMTQ5) exhibit characteristic π-π* absorption around 380 nm and broad intramolecular charge-transfer (ICT) emission in solution (490-502 nm) with photoluminescence quantum yields up to 45% and lifetimes of 2.7-4.0 ns. A detailed solvatochromic and time-resolved study of DMTQ5 confirmed strong ICT character, manifested by red-shifted emission and polarity-dependent lifetime shortening. Electrochemical studies reveal consistent oxidation onsets (0.54-0.64 V vs Fc/Fc+), corresponding to HOMO levels of -5.34 to -5.44 eV, while LUMO energies (-2.57 to -2.67 eV) were derived from optical gaps of ∼2.8 eV. In the solid state, spin-coated films of selected derivatives exhibit pronounced photochromic switching of emission colour and intensity, a behaviour absent in solution and directly demonstrated using UV-LED excitation. These results establish fluorene substitution as a versatile strategy to direct emissive behaviour in quinoxaline-based chromophores, highlighting their potential as polarity-sensitive probes, light-responsive coatings, and optoelectronic materials.